Teachers' Beliefs and Classroom Practices in Malaysian ESL Secondary Classroom - Collin, Jerome; Moses Stephens Gunams, Samuel (2014)
Numerous studies have examined the complex relationship between teachers’ pedagogical beliefs and classroom practices particularly the ways in which these practices do not always converge with teachers’ beliefs and the plethora of factors that govern such relationship (see Borg, 2003; Breen et al., 2001; Farrell & Lim, 2005; Gatbonton, 2008 ). The research presented in this paper seeks to examine this complexity by investigating the extent of convergence and divergence in a Malaysian ESL teacher’s pedagogical beliefs and classroom practices , and the contributing factors to the phenomenon . A case study of a novice female secondary school teacher teaching English to low -intermediate level learners in two lessons was conducted. The teacher’s beliefs about language learning and teaching were obtained via a questionnaire using Likert-scale, while the classroom practices were analysed from video recordings of the two lessons. The questionnaire analysis showed that the teacher’s beliefs not only exemplified those of novice teachers, but closely mirrored those who have extensive experience in the profession. The analysis of video recordings revealed that the teacher’s classroom practices converged with her beliefs about language teaching and learning, indicating the need to rethink current research on pedagogical beliefs and practices among experienced an d novice ESL teachers. Time constraint, teaching experience, perceptions of student learning and other possible factors that govern the relationship are also discussed.